(untitled) (Research, Society and Development, 2022)
Introduction: with the colorectal cancer removal procedure, there is a need to create an ostomy, an orifice that can lead to several biopsychosocial changes, with limited sexuality. This article is an integrative review on the sexuality of people with an ostomy, a subject that is not currently addressed, and whose guiding question was: “What has been produced by researchers in the last five years, about the sexuality of people stoma? ”, objective: identify in scientific production what they bring about the sexual aspects of the person with a stoma. Methodology: a search was performed in the PubMed and BVS database, with the descriptors "ostomy", "sexuality" and "nursing" respecting pre-established criteria, and obtaining a total of 14 articles for analysis and complete reading. Results: the ostomy leads to a series of internal questions regarding self-perception, decreasing the sexual activity in this population, in addition to the fact that with surgery there may be a decrease in libido and erectile dysfunction in men, decreased lubrication and discomfort during sex in therefore, the health professional must be attentive to the needs of this population, providing better adaptation in sexual activity.